Progress in Vocal Fold Regenerative Biomaterials: An Immunological Perspective. Issue 2 (18th December 2021) - Coburn, Patrick T.; Li, Xuan; Li, Jianyu; Kishimoto, Yo; Li-Jessen, Nicole Y. K.
Abstract : Vocal folds are important to daily breathing, speech, and swallowing functions. Irreversible changes to the vocal fold mucosa, such as scarring and atrophy, require regenerative medicine approaches to promote controlled regrowth of the mucosa. Various biomaterial systems have been engineered with an emphasis on stimulating extracellular matrix production from local fibroblasts. Simultaneously, it is imperative to minimize the foreign body response and associated inflammation that can hinder biomaterial−tissue integration. Biomaterial designs have become increasingly focused on actively harnessing the immune system to accelerate and optimize tissue regeneration. An array of biomaterial parameters have been reported to effectively modulate local immune cells, such as macrophages, to initiate tissue repair and restore the function of the vocal folds. In this perspective article, the unique immunological profile of the vocal folds is first reviewed. Key physical and chemical biomaterial properties relevant to immunomodulation are then highlighted and discussed. A further examination of the physicochemical properties of recent vocal fold biomaterials follows to generate deeper insights into corresponding immune‐related outcomes. Finally, a perspective will be offered on the opportunity of integrating material‐driven immunomodulatory strategies into future vocal fold tissue engineering therapies. Abstract : Scarring of the vocal fold mucosa continues to confound clinicians. In recent years, a number of biomaterial therapeutics have been proposed to counteract this failed healing and induce tissue healing. Detailed here is a discussion of how material‐driven immunomodulation can be, and has been, utilized in the vocal folds to guide immune activities toward healing and resolution.